Optimizing Student Engagement and Skills through Meta Virtual Project-Based Networked Learning in Digital Environments - Khusnul Khotimah; Sumarno, Alim; Citra Fitri Kholidya; Jang Ho Son; Sitompul, Nurmida Chaterine (Universitas Pendidikan Ganesha, 2025)
This research investigated the impact of the Meta Virtual Project-based Networked Learning (Meta VPNL) model on student performance within a virtual learning environment (VLE) in the subject of The Development of Audio/Radio Media at the State University. The study aimed to address the problem of low student engagement and practical skills development in traditional VLEs. By integrating meta-learning, project-based learning (PjBL), and networked learning, the Meta VPNL model sought to enhance student engagement, collaboration, practical skills, and self-regulation. Qualitative data were collected through reflective journals, focus groups, and observations. The findings indicated that the Meta VPNL model significantly increased student engagement and motivation due to its hands-on, real-world projects. Students developed better collaboration and communication skills, with many reporting improved teamwork and problem-solving abilities. Practical skills related to the subject also showed marked improvement, demonstrating the model's effectiveness in bridging the gap between theoretical knowledge and practical application. Furthermore, students exhibited increased self-regulation and meta-learning skills, becoming more autonomous learners. Despite these positive outcomes, challenges in time management and balancing coursework were noted, highlighting the need for additional support. The study suggests practical actions for educators, institutions, and students to enhance the learning experience. Integrating artificial intelligence (AI) into the Meta VPNL model could offer personalized learning experiences and facilitate effective collaboration, presenting an exciting opportunity for future improvement. The Meta VPNL model proved a practical approach for enhancing student performance in VLEs.